GEOGEBRA SEBAGAI PENUNJANG PEMBELAJARAN DAN PENINGKATAN KEMAMPUAN SPASIAL - Novianti, Metia; Alghozi, Hakiimul Hilmiy; Suratman, Dede (UNIVERSITAS TANJUNGPURA, 2024)
The ability to understand space and spatial relationships between objects has a significant relationship in human daily life. Not a few studies that have been conducted show that GeoGebra is one of the many media that are said to support the improvement of spatial abilities. Thus, this study is designed to examine and review the extent of the use of GeoGebra in improving spatial abilities. This Systematic Literature Review aims to provide a comprehensive description through analysis of the application of GeoGebra to spatial abilities in the context of mathematics learning, using a literature review approach. Data were collected by documenting and reviewing 49 relevant articles on the use of GeoGebra in improving spatial skills in the period 2017-2024 published in Sinta indexed journals that can be accessed and downloaded on the Google Scholar database. After the selection process, 14 literatures were used for further analysis. The results revealed that the utilization of GeoGebra has a positive impact, effective, and more efficient in improving the spatial abilities of students. In addition, GeoGebra can be developed into learning media that can support optimizing the development of students' spatial abilities.